Sosialisasi dan Pendampingan Pencegahan Penularan Covid 19 Dikalangan UMKM Untuk Meningkatkan Kepercayaan Konsumen di Kota Cimahi - Harun Heri Trismiyanto; Ali Taufan; Iing Nurdin (Training & Research Institute - Jeramba Ilmu Sukses, 2021)
This article begins with the uniqueness and problems related to the socialization and assistance for preventing transmission of Covid 19 among small and medium micro-enterprises (MSMEs) in Cimahi City. It can be seen from Covid 19 transmission, which has not been completed until now. The purpose of the community is to provide socialization and assistance regarding the prevention of transmission of Covid 19 and the use of personal protective equipment in MSMEs in the city of Cimahi. The method used is descriptive-qualitative. It is sampling through purposive sampling. Secondary data collection techniques through regulations and the collection of primary data through observation and in-depth interviews to MSMEs in Cimahi City. This community service is conducted online through virtual media for training and offline, namely conducting face-to-face training directly by paying attention to health protocols. The validity of the data in this study was obtained by conducting credibility testing using triangulation as checking results from various sources of informants. The study results in this community service activity have similar perceptions in preventing transmission of Covid 19 in MSMEs that are more targeted by utilizing the Cimahi City MSME for prevention of Covid transmission 19.